2020
DOI: 10.3389/frobt.2020.00025
|View full text |Cite
|
Sign up to set email alerts
|

Attraction, Dynamics, and Phase Transitions in Fire Ant Tower-Building

Abstract: Many insect species, and even some vertebrates, assemble their bodies to form multi-functional materials that combine sensing, computation, and actuation. The tower-building behavior of red imported fire ants, Solenopsis invicta, presents a key example of this phenomenon of collective construction. While biological studies of collective construction focus on behavioral assays to measure the dynamics of formation and studies of swarm robotics focus on developing hardware that can assemble and interact, algorith… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 61 publications
0
1
0
Order By: Relevance
“…structures such as towers nucleated about substrates [20]. While the behaviour and flow of 3D ant towers has been examined [20,21], questions remain regarding the long-term dynamics of approximately two-dimensional (2D) rafts. Mlot et al [11] reported that, upon being placed into the water as approximately 3D spheroids, ant rafts spread out rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…structures such as towers nucleated about substrates [20]. While the behaviour and flow of 3D ant towers has been examined [20,21], questions remain regarding the long-term dynamics of approximately two-dimensional (2D) rafts. Mlot et al [11] reported that, upon being placed into the water as approximately 3D spheroids, ant rafts spread out rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…Free boundary problems arise in other natural processes, including, but not limited to, dendritic crystal growth [30,31] and flame front propagation [32][33][34]. Continua may also be used to model other collective behaviours [4,35,36] such as fish schooling [37], bird flocking [38], bat swarming [39,40] and ant colony formation [41,42].…”
Section: Introductionmentioning
confidence: 99%